Rising Multidrug-Resistant Pathogens in Pediatric Appendicitis: A Decade-Long Study from Southern Israel - Melamed, Rimma; Ozalvo, Doreen; Sagi, Orli; Assi, Zaki; Nahom, Antonella; Kezerle, Yarden; Novack, Lena; Shany, Eilon (European Journal of Pediatric Surgery, 2025)
Appendicitis is the most common indication for emergent abdominal surgery in childhood. Intravenous antibiotic therapy reduces infections-related complications. Epidemiological data concerning bacterial pathogens are important in tailoring antibiotic stewardship recommendations.This study aims to assess trends over the years in bacterial distribution, and sensitivities (specifically multidrug-resistant [MDR] Enterobacteriaceae) in surgical appendicitis among two different ethnic communities in southern Israel.This was an observational, single-center, retrospective study. Included were children less than 18 years of age with surgical appendicitis treated in Soroka University Medical Center between 2010 and 2020 that had a positive intraoperative intraperitoneal bacterial swab culture. Data were assessed using univariable and multivariable analyses including multiple linear regression and negative binomial regressions with time series analysis to compare between periods during the study while accounting for confounders.Overall, 1,858 specimens were available for analysis from 2,264 children with confirmed surgical appendicitis. Pathogenic bacteria were recovered in 684 (36.8%), with nearly half polymicrobial. MDR Enterobacteriaceae pathogens were more common in the Arab–Bedouin community as compared with the Jewish community (32.6% vs. 18.6%, p < 0.001). Time series analysis detected an 8.7% significant increase in MDR pathogens per year (p = 0.003) with male children (10% per year [p = 0.016]), children younger than 12 years (10% per year [p = 0.014]), and children of the Arab-Bedouin community (8.7% per year [p = 0.025]) accounting for this increase in MDR isolates.MDR pathogens incidence has significantly increased between 2010 and 2020 and this should be considered in the choice of antibiotic therapies and antibiotic stewardship programs in the hospital and the community.
Keywords: children; appendectomy; infection; multidrug resistance; antibiotic stewardship